2009
DOI: 10.1016/j.jacc.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Assessment of Pulmonary Arterial Hypertension

Abstract: The diagnosis and assessment of pulmonary arterial hypertension is a rapidly evolving area, with changes occurring in the definition of the disease, screening and diagnostic techniques, and staging and follow-up assessment. The definition of pulmonary hypertension has been simplified, and is now based on currently available evidence. There has been substantial progress in advancing the imaging techniques and biomarkers used to screen patients for the disease and to follow up their response to therapy. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
735
0
35

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,022 publications
(787 citation statements)
references
References 160 publications
8
735
0
35
Order By: Relevance
“…PH is defined as a resting mean pulmonary artery pressure (mPAP) Ն25 mm Hg at right heart catheterization; PAH is defined as PH in addition to pulmonary capillary wedge pressure (PCWP) Յ15 mm Hg (27). A hemodynamic evaluation was performed during maximal exercise for patients without resting PH.…”
Section: Methodsmentioning
confidence: 99%
“…PH is defined as a resting mean pulmonary artery pressure (mPAP) Ն25 mm Hg at right heart catheterization; PAH is defined as PH in addition to pulmonary capillary wedge pressure (PCWP) Յ15 mm Hg (27). A hemodynamic evaluation was performed during maximal exercise for patients without resting PH.…”
Section: Methodsmentioning
confidence: 99%
“…The 6-minute walk test has been found to be a significant prognostic indicator in several cardiopulmonary diseases such as COPD, congestive heart failure, and pulmonary hypertension. 2123 Physical inactivity has been associated with an increased risk of VTE in the past. The Nurses’ Health Study, following 69,950 female nurses for an average of 18 years, found that those that were the most sedentary were 2 to 3 times more likely to develop an unprovoked VTE compared to those that were the least sedentary.…”
Section: Discussionmentioning
confidence: 99%
“…36 Generally only 10-15% of iPAH patients show a positive acute vasoreactive response and about half of them will continue to respond to calcium channel blockers over a long period of time. 1 In a recent study, Sitbon and colleagues showed that of 12.6% patients with iPAH who displayed acute pulmonary vasoreactivity, only 54% had a sustained, long-term benefit with oral calcium channel blockers as monotherapy. 37 Hence overall <7% of 557 patients with iPAH were long-term responders.…”
Section: Vasodilator Challengementioning
confidence: 99%
“…1 It is a progressive disease involving small pulmonary arteries and is characterised by vascular proliferation and remodelling. The pulmonary vascular resistance (PVR) gradually rises, often leading to right heart failure and death.…”
Section: Introductionmentioning
confidence: 99%